Analisis Perilaku Konsumen Terhadap Keputusan Pembelian Produk Roti Jordan Di Kota Mataram - Sesi Ana Tasia; Baiq Herdina Septika; Yayang Erry Wulandari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to analyze cultural factors, social factors and personal factors in decision making. This research uses quantitative methods. The sample in this research was 100 people. The analysis method uses analysis tools with the help of the SPSS Output Interpretations program. The results of this F Test research show that there is a positive and significant influence of Cultural Factors, Social Factors and Personal Factors simultaneously (simultaneously) on the decision to purchase Jordan bread with a calculated f value (75.439) > greater than the F table value (2,699) and significant value (0.000). Furthermore, based on the results of the T Test for the Cultural Factor variable (X1), the Tcount value (2.093) is > greater than the Ttable value (1.984), with a significant t value of (0.039) > greater than the value (0.05), so it can be it was concluded that Cultural Factors (X1) personally had a significant influence on purchasing decisions (Y) for Jordan bread. while the Social Factor variable (X2) obtained a Tcount value of (3.029) > greater than the Ttable value (1.984) and a significant t value of (0.03) <smaller than (0.05), so it can be concluded that the Social Factor ( X2) partially has a significant effect on Purchase Decisions (Y) on Jordan Bread. And the Personal Factor variable (X3) obtained a Tcount value (7.948) > greater than the Ttable value (1.984) and a significant t value of (0.00) <smaller than (0.05) so it can be concluded that the Personal (Personal) (X3) partially has a significant influence on Purchase Decisions (Y) on Jordan Bread